Evaluating the ecological suitability for Olive tree in Sichuan using GIS and comprehensive fuzzy method: Methodological development and application - Guo, Xiang; Yan, Dong; Fan, Jianrong; Zhu, Wanze; Li, Mai-He (Computing in science & engineering, 2019)
We have used the Geographic Information System’s (GIS) spatial analysis functions and comprehensive fuzzy sets to evaluate and analyze the ecological suitability of the olive trees in Sichuan, China. The over-years experience of olive planting and amelioration data has also been used as an aid to this analysis taking consideration of climate, soil, and topography which are closely related to the olive growing habit. The results are representing the actual distribution of olive while providing alternative adaptive regions for olive growing, thus we are able to offer guidance for the olive cultivation in the region.